2001
DOI: 10.1186/1471-2466-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum and bronchoalveolar lavage fluid sialic acid levels between malignant and benign lung diseases

Abstract: Background: It is known that tissue and serum sialic acid levels may be altered by malignant transformation. In this study, sialic acid levels were determined in bronchoalveolar lavage fluid (BAL) and serum in two groups of patients with lung cancer and non-malignant diseases of the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…В литературе имеются противоречивые данные, согласно которым содержание сиаловых кислот в крови больных раком легкого значимо превышает аналогичные показатели у здоровых доноров, а также у пациентов с неопухолевыми заболеваниями легких [19]. Однако значимых отличий уровня сиаловых кислот в крови и жидкости бронхиального лаважа у пациентов с раком легкого и неопухоле-выми заболеваниями не найдено [20]. Увеличение уровня сиаловых кислот в крови при раке легкого положительно коррелирует с метастазированием данной опухоли [21].…”
Section: Discussionunclassified
“…В литературе имеются противоречивые данные, согласно которым содержание сиаловых кислот в крови больных раком легкого значимо превышает аналогичные показатели у здоровых доноров, а также у пациентов с неопухолевыми заболеваниями легких [19]. Однако значимых отличий уровня сиаловых кислот в крови и жидкости бронхиального лаважа у пациентов с раком легкого и неопухоле-выми заболеваниями не найдено [20]. Увеличение уровня сиаловых кислот в крови при раке легкого положительно коррелирует с метастазированием данной опухоли [21].…”
Section: Discussionunclassified
“…On the contrary, Isitmangil et al (2001) reported that sialic acid levels in bronchoalveolar lavage fluid and serum did not show any statistically significant difference between subjects with malignant and the non-malignant lung diseases (p > 0.05). Sialic acid levels were also unrelated to the stage and localization of the tumor (p > 0.05).…”
Section: Discussionmentioning
confidence: 87%
“…In the current study, the main purpose of using combined measurement of tumor markers is to eliminate the false negative and false positive results as reported by many authors 10,18 . After reviewing our results as well as those of others, the question on the usefulness of combining markers in assessing early diagnosis of malignant liver disease is raised.…”
Section: Figure 1: Multiple Roc Curves For Afp Pivka-ii Vegf Sialimentioning
confidence: 98%